Perencanaan Jalur Rel Lingkar Luar Api Madiun Menggunakan Autocad Civil 3D - Aghastya, Adya; Adi, Wahyu Tamtomo (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
Indonesian Railroad Academy Madiun is one of the education UPTs under the Ministry of Transportation which houses the railway sector. To support education in the Madiun API and in accordance with the 2017 Revised Madiun API Master Plan, it is necessary to have additional lines, namely the Madiun API outer ring. Autocad Civil 3D software is very useful in providing an innovative, effective and efficient solution in the process of planning civil engineering specifically for the manufacture of railroad lines so that it is easier, faster and lower cost with the methodology of working on inputting land survey data and carrying out the next alignment design automatically cutting pieces of data transverse, longitudinal, gallian volume and auto fill have been obtained. The planning data that is the speed of the plan used is 30 km / h with a track width of 1,067m. design length of 1234,187m with a slope of 0,0009 or 0.09% below the maximum standard of 10 per ‰, cumulative fill 15584.68 m³ and comulative cut 5719.08 m³.